La libertad de cátedra y la universidad que innova - Campos Retana, Roy (Universidad de Costa Rica, 2020)
Although the university was born as an institution that fostered the growth of the spirit and sake the truth, time forced her to change into a new educational paradigm. This transformative process fosters her to innovate in their didactic strategies, to change the pedagogical model, integrating software and hardware platforms. Therefore, the university faced an identity crisis. Besides pursuing truth, the university entered a survival mode for trying to keep her economic sustainability. Along those lines, the idea of academic freedom as a legal mechanism to protect institutions from external ideologies, universities had always been on the threat of "educational innovation". This paradigm came to push the integration of blended teaching and learning methods within the classrooms. The effectiveness of these methods is still unknown; hence, academic freedom has indeed been swayed. Draggin from the experiences of Germany, Spain, and Costa Rica, this essay explores how academic freedom can resist government and university to overcome the authority of the professor. Nevertheless, we conclude considering how academic freedom is a relatively capable medium to achieve autonomy